Interreligious Dialogue, Conflict Resolution and Peacebuilding: A Review - Michael Daniel Driessen (Religions)
Over the last twenty years, policymakers and practitioners have supported the growth of multiple interreligious initiatives aimed at peacebuilding and conflict resolution, and scholars have sought to understand and evaluate their efficiency. This article introduces and reviews the emerging scholarship which has developed to understand and analyze these efforts. It begins by drawing from recent empirical research to outline how scholars understand religion as being linked to conflicts and naming a number of initiatives that have been constructed as responses to them. The article then considers how interreligious dialogue could be understood to serve as a conduit for conflict mediation and peacebuilding. Finally, the paper discusses several persistent criticisms that have been raised about interreligious dialogue as a model of conflict resolution, especially in light of the ongoing wars in Ukraine and Gaza, and ends with some reflections about contemporary strategies for interreligious peacebuilding in light of them.